GAMBARAN KEJADIAN LUKA BAKAR DAN TINGKAT PENGETAHUAN IBU TENTANG PERTOLONGAN PERTAMA LUKA BAKAR PADA ANAK USIA TODDLER DI DESA PADANGSAMBIAN KLOD - Ni Made Krisna Dewi Widya Permata Adi; I Kadek Saputra; Ni Luh Putu Eva Yanti (Coping: Community of Publishing in Nursing, 2021)
Incidence of burns is a fairly common occurrence in toddler age, and mostly occur at home. Mothers who have close relationships with children have a very important role in providing physical, psychological and emotional protection for children. Action that mothers can give when child has a burn is giving first aid to prevent disability in children. This study aimed to describe the incidence of burns and knowledge level of mothers about first aid burns among toddlers in Padangsambian Klod Village. This research was a quantitative research methods with sample was 62 mothers. The sampling technique was probability sampling with a simple random sampling method. Data on the incidence of burns and knowledge level of mothers were collected using a questionnaire that compiled by the researchers. The result shows that the respondents in age 26-35 years were 42 people and last education were high school or equivalent were 31 people. Meanwhile, children in age range of 2 - 3 years with the number of 31 respondent for each boy and girls. Percentage of burn incidents in this study was 3.2% and knowledge level of mothers was in the sufficient category. Some mothers have a missunderstanding of first aid burns because they consider ice cubes, ice water compresses, and toothpaste to be used to heal wounds. Further researchers are expected to be able to increase the number of samples and develop a questionnaire so they can assess more about the incidence of burns and knowledge level of mothers about first aid.